From Dusk till Dawn: Reflections on the Impact of COVID-19 on the Development Practices of a R&D Project - Mendonça, Walter Lucas Monteiro de; Costa, Pedro Henrique Teixeira; Cançado, Emille Catarine Rodrigues; Lima, Fernanda; Canedo, Edna Dias; Bonifácio, Rodrigo; Amaral, Luis Henrique Vieira (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
Responding to change over following a plan is one of the Agile Manifesto's values. According to its original perspective, development teams should embrace changes due to a better understanding of the business domain or about the users' needs. This kind of change is well understood and explored by practitioners and researchers. However, the issue of how development teams embrace changes due to unexpected, severe, and atypical external events (like the ones we are facing during COVID-19) have not been fully discussed. In this paper, we present our experience in managing the expectations and changing the development methods to mitigate the risks of carrying out a research and development project (named Virtual Social Office-VSO) during a pandemic time. To this end, we report on an observational study that explains the main differences between the procedures we expected to follow before the pandemic and the procedures we are following. We also present the perceptions of both stakeholder and development teams about the impact of COVID-19 on VSO development. Although the development team quickly adapted itself to work from home, we observed some impact on the development plans. In particular, trying to reconcile the trade-offs between completeness and the tight schedule for the first release was a challenge, since we depended on different partners to collect the information that we need to make available in a mobile application (app) that corresponds to one of the VSO project outcomes. According to one stakeholder, the initial effort to design and prototype the VSO app (using the Design Thinking approach) before the start of the pandemic, has been considered essential to mitigate part of the threats that arose due to the COVID-19. We discuss part of these threats in this paper and the actions we have been taking to mitigate them. In addition, according to members of the development team, working remotely presents both challenges (e.g., adapt to a new routine, prepare a comfortable place, isolation feelings), and benefits (e.g., working hours flexibility, less distraction from co-workers).